2020
DOI: 10.2147/idr.s247587
|View full text |Cite
|
Sign up to set email alerts
|

<p>Drug Therapy Problems and Predictors Among Patients Admitted to Medical Wards of Dilla University Referral Hospital, South Ethiopia: A Case of Antimicrobials</p>

Abstract: Patients and Methods: A hospital-based prospective observational study design was employed to assess the antimicrobial use-related problems among adult patients admitted to Dilla University Referral Hospital from 5 March to 4 September 2018. The antimicrobial therapy was reviewed to assure compliance with the recommendations of the national guidelines or evidence-based international clinical guidelines and drug therapy problem was identified. The logistic regression model was fit to determine the association b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
1
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 20 publications
3
1
2
Order By: Relevance
“…Logistic regression analysis showed that the number of drugs prescribed per patient (≥5 prescribed drugs) was strong one predictor of the occurrence of DRP. The finding was consistent with the study in Hong Kong [ 26 ], Singapore [ 30 ], Dilla University Referral Hospital [ 25 ], and Jimma University Specialized Hospital [ 29 ]. The reason might be the potential drug-drug interaction as the results of polypharmacy.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Logistic regression analysis showed that the number of drugs prescribed per patient (≥5 prescribed drugs) was strong one predictor of the occurrence of DRP. The finding was consistent with the study in Hong Kong [ 26 ], Singapore [ 30 ], Dilla University Referral Hospital [ 25 ], and Jimma University Specialized Hospital [ 29 ]. The reason might be the potential drug-drug interaction as the results of polypharmacy.…”
Section: Discussionsupporting
confidence: 92%
“…In this study, unnecessary drug therapy 92 (27.79%), non-adherence 57 (17.22%), and dose too high 56 (16.92%) were most frequently encountered DRPs. The finding was consistent with the study of Dilla university referral hospital in which non-adherence was the most occurred types of DRP 68(29.69%), and ADR was the least type of DRP 7(3.06%) [ 25 ]. Additionally, the study at the University of Gondar reported inappropriate dose was the prevalent DRP [ 7 ] and in India, ADR was the least occurred type of DRP (1.39% [ 4 ].…”
Section: Discussionsupporting
confidence: 91%
“…The prevalence of at least one antimicrobial use-related DTP in this study (76.6%) is comparable with the studies done at the medical wards of Jimma University Specialized Hospital (75.7%), 20 Dessie Referral Hospital (75.5%), 15 Wollega University Referral Hospital (71.5%), 21 and Dilla University Referral Hospital (70.7%) 22 that revealed at least one antimicrobial use-related DTP. This might be due to the existence of health facilities at a similar level.…”
Section: Discussionsupporting
confidence: 86%
“…The next frequently seen antimicrobial use-related DTP in our study was the need for additional drug therapy (28.1%), which is comparable to the studies done in Jimma University Specialized Hospital (29.6%), 20 and Mizan, Bonga, and Tepi Hospitals of southwest Ethiopia (31.3%). 27 However, the need for additional drug therapy in our study was higher than that of studies conducted at Dilla University Referral Hospital (13.5%) 22 and Wollega University Referral Hospital (22.8%). 21 This may be due to failure to give preventive drug therapy to reduce the risk of developing a new condition and additional drug therapy to attain synergistic or additive effects.…”
Section: Discussioncontrasting
confidence: 61%
“…Though the occurrence rate of DRPs is more frequent in the intensive care unit (ICU) due to the complicated medical condition and the associated complexity of drug therapy [ 19 ], studies assessing it on hospitalized neonatal are highly limited [ 14 , 17 ]. In Ethiopia, a study found that the extent of DRPs in infectious disease patients was as high as 70.7% [ 20 ] and studies have shown that neonatal sepsis is the most common reason for admission to the NICU in the range of 22.7–28.6% [ 21 , 22 ] and cause of death between 4.1 and 18.4% [ 22 , 23 ]. Despite this, no previous studies have addressed the magnitude of DRPs and their impact on neonates hospitalized at the NICU in Ethiopia.…”
Section: Introductionmentioning
confidence: 99%